Avoidable Waste in Ophthalmic Epidemiology: A Review of Blindness Prevalence Surveys in Low and Middle Income Countries 2000–2014. (2nd January 2018) - Ramke, Jacqueline; Kuper, Hannah; Limburg, Hans; Kinloch, Jennifer; Zhu, Wenhui; Lansingh, Van C.; Congdon, Nathan; Foster, Allen; Gilbert, Clare E
ABSTRACT: Purpose : Sources of avoidable waste in ophthalmic epidemiology include duplication of effort, and survey reports remaining unpublished, gaining publication after a long delay, or being incomplete or of poor quality. The aim of this review was to assess these sources of avoidable waste by examining blindness prevalence surveys undertaken in low and middle income countries (LMICs) between 2000 and 2014. Methods : On December 1, 2016 we searched MEDLINE, EMBASE and Web of Science databases for cross-sectional blindness prevalence surveys undertaken in LMICs between 2000 and 2014. All surveys listed on the Rapid Assessment of Avoidable Blindness (RAAB) Repository website ("the Repository") were also considered. For each survey we assessed (1) availability of scientific publication, survey report, summary results tables and/or datasets; (2) time to publication from year of survey completion and journal attributes; (3) extent of blindness information reported; and (4) rigour when information was available from two sources (i.e. whether it matched). Results : Of the 279 included surveys (from 68 countries) 186 (67%) used RAAB methodology; 146 (52%) were published in a scientific journal, 57 (20%) were published in a journal and on the Repository, and 76 (27%) were on the Repository only (8% had tables; 19% had no information available beyond registration). Datasets were available for 50 RAABs (18% of included surveys). Time to publication ranged from <1 to 11 years (mean, standard deviation 2.8 ± 1.8 years). The extent of blindness information reported within studies varied (e.g. presenting and best-corrected, unilateral and bilateral); those with both a published report and Repository tables were most complete. For surveys published and with RAAB tables available, discrepancies were found in reporting of participant numbers (14% of studies) and blindness prevalence (15%). Conclusion : Strategies are needed to improve the availability, consistency, and quality of information reported from blindness prevalence surveys, and hence reduce avoidable waste.